A Facile Liquid Alloy Wetting Enhancing Strategy on Super‐Hydrophobic Lotus Leaves for Plant‐Hybrid System Implementation. Issue 17 (27th April 2022) - Jiang, Jiajun; Fei, Wenjie; Pu, Menghao; Chai, Zhiping; Wu, Zhigang
Abstract: Plant‐hybrid systems have demonstrated exciting opportunities in plant health sensing, climate monitoring, and energy harvesting, endowing great prospects for connecting plants to man‐made digitalized world. Due to its intrinsic softness/stretchability, biocompatibility, and non‐invasion, liquid alloy has shown great advantages in plant‐hybrid system implementation. However, many widely seen plant organisms having micro‐nano surface structures and waxy layer, e.g., lotus leaves, showing super‐hydrophobic behavior, prevent the liquid alloy adhesion and further its implementation of plant‐hybrid systems. By introducing a low‐concentration soap solution as an intermediate layer onto super‐hydrophobic leaves, the authors thereby propose a facile liquid alloy wetting enhancing strategy and well print liquid alloy circuits on the leaves to form plant‐hybrid systems. Surfactants (in the soap) enhance the wetting ability of solution on the lotus leaf surface, and subsequently the attracted water on the leaf surface contributes to make liquid alloy adhered on super‐hydrophobic leaves. Furthermore, the authors demonstrate the liquid alloy plant‐hybrid implementation based on the lotus leaves for the perception of human body, and set a system as a home intrusion alarm. This work presents an excellent example of digitalized integration on super‐hydrophobic plant organisms, which provides a new tool technology for plant‐hybrid implementations and broadens the digitalized application range of plants. Abstract : A liquid alloy wetting enhancing strategy is proposed to print liquid alloy circuits onto the super‐hydrophobic lotus leaves by introducing a facile low‐concentration soap solution. Based on the strategy, a practical plant‐hybrid system for home intrusion alarm is demonstrated, which paves a simple yet effective tool technology for plant‐hybrid implementations.